Penafsiran Peran Politik Perempuan: Kritik Fatima Mernissi Perspektif Feminis - Maksum, Ghufron; Afiyah, Nur; Alwasi, Naila Magfira (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2025)
This research explores Fatima Mernissi's criticism of women's political roles in the Qur'an through a feminist approach. The focus of the research lies on analyzing the discourse of Qur'anic interpretation which, according to Mernissi, often reproduces patriarchal narratives that limit women's participation in the political sphere. The purpose of the study is to evaluate how the Muslim feminist perspective, Mernissi reveals the bias of traditional interpretations and offers a more egalitarian reinterpretation of the Qur'anic text. This research uses a library research method with a critical text analysis approach to Mernissi's works and classical and contemporary Qur'anic interpretations. The data is analyzed with a feminist approach to identify patterns of gender bias in the interpretation of certain verses related to politics and women's leadership. The results showed that Mernissi's criticism succeeded in deconstructing traditional interpretations that tend to rule out the potential of women in politics, while emphasizing that the Qur'an actually opens space for equal gender roles. The conclusion of this study emphasizes the importance of a feminist approach to reconstructing the understanding of sacred texts, so that they are more relevant in supporting gender inclusivity and justice in the modern political context.